Analysis of energy production with different photovoltaic technologies in the Colombian geography (2014)
This research has analyzed the photovoltaic technologies, Polycrystalline silicon, Monocrystalline Silicon, GIS, Cadmium Tellurium and Amorphous Silicon; in eight cities of the Colombian territory, in order to obtain a clear idea of what is the most appropriate for each city or region studied. PVsyst simulation software has been used to study in detail each photovoltaic technology, for an installed capacity of 100kW knowing the specific data of losses by temperature, mismatch, efficiency, wiring, angle inclination of the arrangement, among others